Activation of Nrf2/HO-1 Pathway by Nardochinoid C Inhibits Inflammation and Oxidative Stress in Lipopolysaccharide-Stimulated Macrophages - Luo, Jin-Fang; Shen, Xiu-Yu; Lio, Chon Kit; Dai, Yi; Cheng, Chun-Song; Liu, Jian-Xin; Yao, Yun-Da; Yu, Yang; Xie, Ying; Luo, Pei; Yao, Xin-Sheng; Liu, Zhong-Qiu; et al. (Frontiers in Pharmacology, 2018)
Abstract The roots and rhizomes of Nardostachys chinensis have neuroprotection and cardiovascular protection effects. However, the specific mechanism of N. chinensis is not yet clear. Dinardokanshone C is a new compound with new backbone isolated from N. chinensis and this study for the first time explored the anti-inflammatory and anti-oxidant effect of dinardokanshone C. The results showed that dinardokanshone C significantly reduced the release of nitric oxide (NO) and prostaglandin E2 (PGE2) in lipopolysaccharide (LPS)-activated RAW264.7 cells. The expression of pro-inflammatory proteins including inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were also obviously inhibited by dinardokanshone C. Besides, the production of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were also remarkably inhibited by dinardokanshone C. Furthermore, dinardokanshone C inhibited the macrophage M1 phenotype and the production of reactive oxygen species (ROS). Mechanism studies showed that dinardokanshone C mainly activated nuclear factor-E2-related factor 2 (Nrf2) signaling pathway, increased the level of anti-oxidant protein heme oxygenase-1(HO-1) and thus produced the anti-inflammatory and anti-oxidant effects, which were abolished by Nrf2 siRNA and HO-1 inhibitor. These findings suggested that dinardokanshone C could be a new Nrf2 activator for the treatment and prevention of diseases related to inflammation and oxidative stress. Keywords: Nardostachys chinensis; dinardokanshone C; Nrf2; HO-1; ROS.